PERTIMBANGAN HAKIM PENGADILAN NIAGA JAKARTA PUSAT DALAM SENGKETA MEREK TERKENAL PUTUSAN 121/2022: Judicial Considerations in Famous Trademark Disputes: Analysis of Decision 121/Pdt.Sus/Merek/2022 - Dimas Andrian; Muriani (Faculty of Law, Universitas Trisakti, 2025)
This study evaluates the Commercial Court’s decision in the Fisher-Price trademark dispute, in which Liu Ignasia F. Yulianti duplicated and re-registered the well-known mark. The research examines whether the plaintiff, Mattel Inc., meets the requirements to file a cancellation lawsuit under Article 76 of Law No. 20 of 2016 and whether the Central Jakarta Commercial Court’s rejection in Decision No. 121/Pdt.Sus/Merek/2022/PN.Niaga.Jkt.Pst is legally justified. Using a normative method with descriptive analysis and secondary legal sources, the study finds that Mattel Inc. possesses a valid legal basis to file the lawsuit because Fisher-Price is a well-known mark. The analysis also suggests that the court’s acceptance of the defendant’s exception was inappropriate, indicating an error in judicial consideration.